Integration of character education in android-based m-learning media on problem-solving ability - Ahmad Yani; Utin Desy Susiaty; Agustami Agustami; Hodiyanto Hodiyanto (IKIP PGRI Pontianak, 2022)
This study aims to produce M-learning media that is effective, practical, effective by including character education and the ability to solve problems in the media in cube material and building blocks. This study adopted the ADDIE development design model which included five main stages, namely analysis, design, development, implementation and evaluation. The subject of this study was a grade VIII student of SMP Negeri 10 Sungai Kakap, totaling 15 students. The instruments used in this study were validation sheets, questionnaires, and pretest and posttest questions. The results showed that the average level of verification of mobile learning media by the three experts was 85.56%, meets the very valid criteria. The cumulative score of teacher and student questionnaires reaches 88.66%, very practical. The results of inferential statistical tests from pretest and posttest using the t test, it was found that T_Hitung <-t_table with significant Î± = 5% which means there is a significant difference in the ability to solve problems between before and after using mobile learning media so that it can be said that the media is classified as effective. Therefore, it can be concluded that the use of mobile learning media combined with character education on the ability to solve the geometry problem of junior high school students is valid, practical and effective.